An Electrically Conducting Three‐Dimensional Iron–Catecholate Porous Framework. (1st July 2021) - Mähringer, Andre; Döblinger, Markus; Hennemann, Matthias; Gruber, Christoph; Fehn, Dominik; Scheurle, Patricia I.; Hosseini, Pouya; Santourian, Irina; Schirmacher, Alfred; Rotter, Julian M.; Wittstock, Gunther; Meyer, Karsten; et al.
Abstract: We report the synthesis of a unique cubic metal–organic framework (MOF), Fe‐HHTP‐MOF, comprising hexahydroxytriphenylene (HHTP) supertetrahedral units and Fe III ions, arranged in a diamond topology. The MOF is synthesized under solvothermal conditions, yielding a highly crystalline, deep black powder, with crystallites of 300–500 nm size and tetrahedral morphology. Nitrogen sorption analysis indicates a highly porous material with a surface area exceeding 1400 m 2  g −1 . Furthermore, Fe‐HHTP‐MOF shows broadband absorption from 475 up to 1900 nm with excellent absorption capability of 98.5 % of the incoming light over the visible spectral region. Electrical conductivity measurements of pressed pellets reveal a high intrinsic electrical conductivity of up to 10 −3  S cm −1 . Quantum mechanical calculations predict Fe‐HHTP‐MOF to be an efficient electron conductor, exhibiting continuous charge‐carrier pathways throughout the structure. Abstract : Fe‐HHTP‐MOF, a unique cubic metal–organic framework (MOF) comprising hexahydroxytriphenylene (HHTP) supertetrahedral units and Fe III ions arranged in a diamond topology is reported. Fe‐HHTP‐MOF is a highly crystalline, porous and deep black material featuring high electrical conductivity.